My Family and Other Animals - Durrell, Gerald (UK, 1956)
Fed up of the cold and wet, the Durrell family - diet - obsessed Margo, gun-toting Leslie, bookworm Lawrence and budding naturalist Gerry, together with their widower mother and Roger the dog - abandon British for the island of Corfu. The Durrell find the island is a beautiful paradise, and a cornucopia of wildlife. Inspired to collect scorpions, geckos, toads, bats, butterflies and any other creatures that take his fancy, young Gerald plunges their new home into confusion and chaos...
Keywords: Biography & Autobiography; Gerald Durrell; Non-Fiction